Arabic Language Learning System Based On SPADA DIKTI Indonesia - Rachmawati, Miatin; Nugrahawan, Ahmad Rizki (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2022)
In this researcher will try to provide one of the lessons that attracts students' attention, one of which is the implementation of the SPADA DIKTI account which attracts attention and will find out the effectiveness of the SPADA DIKTI application on this platform, the research method used qualitative research with approach data in this study were included descriptions the primary data source which is carried out with a data collection technique is more on observation. Based on the explanation and data analysis, it was found that: By using an E-Learning. This In this special education menu there are several things related to learning, starting from Homepage, My courses, Vcon, Assigment, Exams, logbook, and presences. Here the researcher will explain one by one the steps of E-Learning at this higher education, especially in learning psycholinguistics courses. In this system the teacher can see the effectiveness of a learning system, the steps in applying a learning system, especially in the E-Learning system, can also help to monitor the seriousness of students take part in learning, especially psycholinguistics starting with the application of Spada Dikti, uploading materials, evaluations and student attendance lists, all neatly and effectively in learning the SPADA DIKTI learning system.